2018
DOI: 10.1038/s41565-018-0255-3
|View full text |Cite
|
Sign up to set email alerts
|

Fast current-driven domain walls and small skyrmions in a compensated ferrimagnet

Abstract: Spintronics is a research field that aims to understand and control spins on the nanoscale and should enable next-generation data storage and manipulation. One technological and scientific key challenge is to stabilize small spin textures and to move them efficiently with high velocities. For a long time, research focused on ferromagnetic materials, but ferromagnets show fundamental limits for speed and size. Here, we circumvent these limits using compensated ferrimagnets. Using ferrimagnetic Pt/GdCo/TaO films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
466
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(510 citation statements)
references
References 54 publications
35
466
3
6
Order By: Relevance
“…The magnetic skyrmion with exceptionally small size is anticipated to remain robust and can be driven by electric currents easily without being interrupted by system disorders such as structural defects [19][20][21][22][23][24][25][26][27][28]. Therefore, it is being considered as a promising candidate for information carrier in the applications for ultrahigh density data storage [19,20,29], logic [30], and neuromorphic [31,32] technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic skyrmion with exceptionally small size is anticipated to remain robust and can be driven by electric currents easily without being interrupted by system disorders such as structural defects [19][20][21][22][23][24][25][26][27][28]. Therefore, it is being considered as a promising candidate for information carrier in the applications for ultrahigh density data storage [19,20,29], logic [30], and neuromorphic [31,32] technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Here we find that the two linear components ( , have different wave vectors in the This difference in the wave vector generates an additional phase shift for spin waves passing 9 through a spin tilted region. The additional phase shift is calculated from the WKB approximation, given as…”
Section: B Easy Axis Aligned With Z Axismentioning
confidence: 73%
“…An important motivation is that spin dynamics in antiferromagnets is much faster than in ferromagnets. Net zero spin density of two antiferromagnetically coupled sublattices suppresses the rotational motion of antiferromagnetic spin textures, which allows antiferromagnetic domain walls move much faster than ferromagnetic domain walls [3][4][5][6][7][8][9][10][11] and also results in vanishing skyrmion Hall effect in antiferromagnets [12,13] or compensated ferrimagnets [14]. Antiferromagnetic exchange interaction between neighboring spin moments provides a high resonance frequency in the terahertz (THz) ranges [15,16] leading to recent research efforts on THz spin oscillators [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The 2D color map of the out-of-plane reduced magnetization (mz) for the 13 nm skyrmion is inserted in Figure 4. In an experiment, Caretta et al [13] found skyrmion size in the range of 10 nm to 30 nm in Pt/GdCo/TaOx with an average DMI of 0.12 mJ/m 2 , which corresponds to an interfacial DMI of about 0.9 mJ/m 2 . With such interfacial DMI, our simulation shows a skyrmion size of ~20 nm at room temperature, which is in good agreement with experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the simulated magnetization of an amorphous Gadolinium-Cobalt ferrimagnet. With near zero magnetization, the skyrmion velocity can reach a high speed near ~1,000 m/s [13]., while near the angular-momentum compensation temperature, the skyrmion Hall effect is vastly reduced [14]. These material advantages make amorphous ferrimagnet an ideal material for spin-based memory and logic devices.…”
Section: Amorphous Ferrimagnetmentioning
confidence: 99%